Effect of Soybean Seeds On Some Physiological And Biochemical Parameters In Ovariectomized Rats - A. A. Hassan E. M. Abdulrasool (College of Education for Pure Sciences, 2011)
Abstract The present study was conducted to investigate the effect of soybean seeds (15g /kg diet) for one month on blood picture, total cholesterol(T-C), high density lipoproteins(HDL), low density lipoproteins(LDL), triglycerides (TG), glucose, alanine aminotrasferase (ALT) and aspartate aminotrasferase (AST) enzymes activity, glutathione(GSH), total proteins, albumin, globulin and body weight in ovariectomized rats(OVX). The rats randomly divided in to three groups (6 rats / group). The first group served as a control, the second group rats at one month aged bilateral ovariectomy were done, and the third group rats at one month aged bilateral ovariectomy were done, and after two months the rats treated with soybean seeds for one month. The result showed that a significant decrease in the total leucocytes count, HDL, GSH and globulin in ovariectomized group compared with control group, with no significant differences in PCV, Hb, differential leucocytes count(DLC), total proteins, albumin and body weight. The current study demonstrated that a significant increase in T-C, LDL, ALT and glucose in ovariectomized rats group compared with control group. Administration of soybean seeds caused a significant increase in total leucocytes count, globulin and body weight compared with ovariectomized group, and a significant decrease in T-C, TG, LDL and glucose compared with ovariectomized group. It could be concluded from this study that administration of soya beans seeds have a beneficial improving of some physiological and biochemical parameters in ovarictomized rats.